Pengaruh Net Profit Margin, Earning Per Share, Return On Assets dan Leverage Ratio Terhadap Harga Saham Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Annisa Nauli Sinaga; Michael Michael; Yuliyani Yuliyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The stock price is determined by the supply and demand of the stock itself. The higher the purchase of these shares the stock price tends to move up and vice versa if more and more are selling these shares the stock price will usually tend to decrease. The purpose of this study is to analyze and test whether Net Profit Margin (NPM), Earning Per Share (EPS) and Leverage Ratio affect stock prices. This type of research is quantitative descriptive with secondary data, the sampling technique used is purposive sampling and the testing method used uses multiple linear regression analysis. The population in this study is 168 manufacturing companies listed on the Stock Exchange in 2016-2018 period. From the research results it is known that the simultaneous Net Profit Margin (NPM) and Earning Per Share (EPS) and Return On Assets (ROA) and Leverage Ratio have a significant and positive effect. While partially, only Earning Per Share (EPS) and Return On Assets (ROA) have a significant and positive effect, while Net Profit Margin (NPM) and Leverage Ratio has no significant and positive effect. Keywords : Net Profit Margin, Earning Per Share, Return On Assets, Leverage Ratio